Muslims can and do celebrate Christmas - Nilufar Ahmed (2017)
Christmas adverts in the UK unofficially mark the start of the seasonal build up.The major UK supermarket, Tesco, released its annual festive advert in the first week of November 2017, showing families across the UK coming together for Christmas. despite the advert showing a range of families, there was one family that seemed to have caught the nation's attention. A scene depicting a Muslim family caused outrage on social media with accusations that Muslims have no place celebrating Christmas. It seems that Muslims are in a bind. If they do not integrate they are criticized and if they do, they are accused of trying to take over traditions they have no right to partake in. The truth is, Muslims enjoy Christmas as much as everyone else and participate in it as cultural festival as part of living and integrating in the UK.